Dos nuevas especies de Phrynopus (Anura: Leptodactylidae) de los bosques nublados de Bolivia - Aguayo Vedia, Cidar Rodrigo (Universidad de Costa Rica, 2001)
We describe two new species of Phrynopus from cloud forests in Cochabamba, Bolivia. The new species are assigned to the P. peruanus group and are characterized by the presence of basal webbing, distinctive coloration, and by having the first finger shorter than the second. The first of these new species was collected near Montepunko in Parque Nacional Carrasco and is known from eight males and six females. Among its distinctive characteristics are round cream-colored glands on its flanks. A second species is known from one male and one female collected near “Zona de Aguirre” near the northwest border of the park. V and X-shaped blotches and a dorsum that is smooth except for dorsolateral and scapular folds characterize this species. Musculature has rarely been described for species of Phrynopus. The species from Montepunko has unusual gular and thigh musculature that is quite unlike other species of the genus.